International North–South Transport Corridor: A Renewed Horizon of Trade Connectivity Between India and Russia - Tripathi, Sandeep; Singh , Urvashi (YSU Journal of International Affairs, 2025)
In the context of shifting geopolitical alignments and evolving regional strategies, Indo-Russian trade relations are entering a new phase of strategic relevance. This paper examines the potential of the International North–South Transport Corridor (INSTC) as both an instrument for enhancing bilateral trade and a broader geopolitical lever. Two central questions guide the analysis: first, how the INSTC can redefine the scale, efficiency, and scope of economic exchange between India and Russia; and second, how it may influence regional power dynamics amid growing global fragmentation. As Western powers increasingly employ trade as a tool of political coercion, and Russia seeks to recalibrate its international partnerships, the INSTC emerges as a critical avenue for fostering strategic autonomy and connectivity. Beyond its economic utility, the corridor reflects a shared ambition to challenge existing power asymmetries and reinforce multipolarity. This study situates the INSTC within a wider set of developments, including China’s expanding footprint, India’s commitment to a rules-based international order, ongoing geopolitical tensions, and Russia’s pursuit of a rebalanced global security architecture. Against this backdrop, a careful reassessment of the INSTC’s strategic value is necessary to understand its implications for the future of Eurasian connectivity and order.
Keywords: Russia; India; transit corridor